Mean intrasellar pressure, visual field, headache intensity and quality of life of patients with pituitary adenoma Pressão intra-selar média, campo visual, intensidade de cefaléia e qualidade de vida em portadores de adenoma hipofisário - Aldo Pereira-Neto; André Meireles Borba; Paulo Andrade de Mello; Luciana Ansanelli Naves; Antônio Santos de Araújo Jr; Luis Augusto Casulari (Arquivos de Neuro-Psiquiatria)
Intrasellar pressure (ISP) measurement technique has recently opened a new line of research in neuroendocrinology. The absolute and mean ISP values were investigated in 25 patients consecutively operated at the Brasilia University Hospital (DF). These data were correlated with serum prolactin levels, number of visual quadrant affected, tumor size, quality of life (measured through the SF-36 scale) and graded headache (measured through the HIT-6 scale). No correlation was observed. The p values were 0.887; 0.137; 0.892; 0.812 and 0.884; respectively. The HIT-6 values were inversely and moderately correlated with total RAND SF-36 and its mental and physical dimensions. A técnica da medida da pressão intra-selar (PIS) abriu, recentemente, uma nova linha de pesquisa em neuroendocrinologia. O objetivo deste estudo foi aferir os valores absolutos da PIS e calcular a pressão intra-selar média (PIM) em uma população de 25 pacientes operados consecutivamente no Hospital Universitário de Brasília (DF). Não se observou correlação significativa entre a PIM e o número de quadrantes visuais comprometidos (p=0,137), área do tumor (p=0,892), nível de qualidade de vida mensurado pela escala SF-36 (p=0,812) e a presença e a intensidade da cefaléia mensurada pela escala HIT-6 (p=0,884). Contudo, o HIT-6 correlacionou-se de forma inversa e intensidade moderada com os valores de HIT-6 e suas dimensões mental e física.